Effect of Current on the Dynamic Responses of Spars Subjected to Random Wave - Kurian, V.J. (2013)
Abstract—In this study, the dynamic analysis of classic and truss spars were investigated both numerically (frequency and time domain analysis) and experimentally in random wave combined with current. The motion responses in surge, heave, and pitch have been evaluated. The spar platforms were modeled as rigid bodies connected to the sea floor by multi-component catenary mooring lines. The wave force calculations were based on the Morison Equation applied at the instantaneous position of the structure. Experimentally, the classic and truss spar model to a scale of 1:100 were tested in random wave combined with current. The trends of the results fairly agreed, thus validating the accura-cy of the numerical model. Keywords-Wave-current interaction; Spar platforms; Numerical analysis; Model tests, Response Amplitude Operator (RAO)